Designing an Animated Film with the Theme of the November 10 1945 Event in Surabaya titled 'The Battle of the Heroic City” - Nasution, Ade Ayu Syafira (Jurnal Vicidi, 2024)
To support children's growth and development, it is necessary to provide education that expands their knowledge. Therefore, it is important to teach them important concepts for their future from an early age. One suitable method of learning for children is 2D animation, which can be an interactive and enjoyable learning tool. Through animations, children can easily understand subjects like Indonesian history without getting bored. These animations utilize characters with chibi-style designs that appeal to children, along with vibrant colors to maintain their interest until the end. Our goal is for children to understand and become familiar with the names of heroes who fought for independence. The chosen media for publishing these animations is suitable for viewing on YouTube Kids, which is tailored to the target audience of children and monitored by parents during viewing. Through YouTube Kids, we can also gather feedback in the form of comments, which may contain critiques and suggestions for improving future animations. Therefore, the aim of this research is to create a historical animation titled "Battle of the Heroes City" targeted at children aged 3-5 years. This research adopts a qualitative research method involving focus group discussions (FGD) and observations of 18 children aged 2-5 years. The results of the research indicate that animation is an effective educational solution for teaching history to children aged 3-5 years.